Apresentação do resumo expandido elaborado em 2019 por meio da IN Proeg n° 01/2023: automação residencial baseada em comportamento utilizando Raspberry Pi - OLIVEIRA, Josemar Lopes (2023)
This work is presented and structured on the regulation of NORMATIVE INSTRUCTION Nº 01/2023 - PROEG/UFPA and RESOLUTION 001/2023 - FEE - May 2023, which talks about the academic guidelines for the standardization and carrying out of the activities of the Final Paper Course – TCC, making its preparation, presentation and defense more flexible. And it regulates the application of the Normative Instruction in the Faculty of Electrical Engineering of the University Campus of Tucuruí. The expanded summary developed from 03/2019 to 10/2019, and presented at the III Congress of Technologies and Development in the Amazon - CTDA, in which one of the activities developed during the execution of the "Domotic Extension Project"is reported, under the guidance of by Professor Jefferson Souza Costa. The project aimed to apply low-cost home automation technologies in the municipality of Tucuruí, motivating the interests of young people and adults in the community for robotics and home automation applications using printed circuits and low-cost microprocessor platforms, such as Arduino, Raspberry Pi , ESP8266 chip NodeMCU, sensors and actuators module. We approach in the summary a residential automation based on behaviors using Raspberry Pi, from the bibliographical studies carried out by the students members of the project. There were several activities developed, from the construction of prototypes to lectures and short courses given in public schools in the municipality of Tucuruí. The results achieved by the project were the development of home automation prototypes, textual productions that led to publications in congresses, and one of these publications is presented in annex A of this work, a study of behavior-based home automation using Raspberry Pi.